The impact of gender differences on learning digital games programming - Aleksić Veljko V. (Zbornik radova (Univerzitet u Kragujevcu. Pedagoški fakultet u Užicu))
The digital gaming industry has been undergoing expansion, and its further development necessitates the education and inclusion of a diverse and competent workforce, including engineers. The labor market shows a significant gender imbalance in favor of men in this field. The aim of the research is to identify the existence of gender differences and behaviors in learning digital games programming in order to reduce, eliminate, or reshape their negative effect on the motivation of female students to direct their education and career towards the field of digital games programming. The research involved 44 information technology students at the Faculty of Technical Sciences in Čačak. The results confirmed the existence of gender differences and highlighted the need to adapt teaching practices and activities to effectively eliminate these negative effects.